Effect of Genetic and Non-genetic Factors on Lactation Traits in Jersey x Sahiwal Crossbred Cattle under Progeny Testing Programme of Chittoor - Mohammad Siraj, Shaik; Venkata Subramanyam, Boddu; Sakunthala Devi, Kopparthi; Suresh Babu, Dasineni; Vani, Sunkara; Eswar Bhavani, Killana (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Data on lactation traits collected from first lactation performance records of 4,877 daughters sired by 176 Jersey x Sahiwal crossbred bulls, maintained by selected field farmers under field Progeny Testing Programme across 24 mandals in Chittoor district, Andhra Pradesh (India), over a period of 10 years (2014 to 2023) were used for genetic analysis of lactation traits viz. 305-day milk yield (305DMY), total milk yield (TMY), lactation length (LL) and peak yield (PY). The overall least-square means for these traits were 2276.46±8.57 kg, 2300.23±9.20 kg, 283.93±0.49 days and 10.23±0.03 kg, respectively. The effect of sire, period and season of calving were found to be highly significant (p<0.01) for all lactation traits. Heritability estimates for these traits ranged from 0.15 to 0.53. Genetic correlations among the traits were highly positive, ranging from 0.72 to 0.99, while phenotypic correlations were moderate to high, varying from 0.21 to 0.87, except between lactation length and peak yield